Bahasa sebagai Cermin Kepribadian: Analisis Psikolinguistik Tokoh Aris dalam Film Ipar Adalah Maut - Aziza, Estika Nurul; Suharsono, Eko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study explores the relationship between language, personality, and the moral identity crisis experienced by the main character, Aris, in the film Ipar Adalah Maut. Using a cognitive and pragmatic psycholinguistic approach, the research seeks to understand how shifts in Aris’s register and speech style reflect his inner conflicts, particularly cognitive dissonance and identity fragmentation. The data were collected through a documentation technique, which involved carefully rewatching the film and transcribing all of Aris’s utterances related to social dynamics, interpersonal relations, and moments of conflict. These utterances were then selected and grouped to facilitate a structured analysis. A descriptive qualitative method was employed to interpret Aris’s speech patterns in a systematic manner. The findings reveal that Aris uses language not merely as a tool for communication but as a strategy for shaping and protecting his public persona. In public settings, he presents himself with controlled and polished language. However, in more personal situations, his speech shifts toward rationalization and emotional manipulation. This change reflects his strong desire to conceal guilt and evade moral responsibility. Quantitative findings showing the limited expression of guilt further support the conclusion that Aris is highly skilled at constructing a “linguistic fortress” to shield himself. Overall, the study highlights the dual function of language: it serves both as a mirror that reflects the speaker’s psychological condition and as a rhetorical mask used to preserve one’s image and justify morally questionable actions